ENHANCING GRID INTEGRATION OF A SINGLE-PHASE SOLAR INVERTER THROUGH ADVANCED CONTROL TECHNIQUES AND REAL-TIME VALIDATION - Anupama Subhadarsini; Babita Panda; Byamakesh Nayak (Journal of Mechanics of Continua and Mathematical Sciences)
This manuscript aims to formulate an innovative method called Covariance Matrix Adaptation Evolution Strategy based Cat Mouse Based Optimization (CMAES-CMBO) integrated with a Hybrid Fast Fuzzy-2-Degree-of-Freedom Fractional-Order Tilt Integral Derivative Controller (CMAES-CMBO-HFF-2DoFFOTIDC) aimed at enhancing the performance of Grid-Interfaced Solar Inverter Systems (GISIS) while reducing total harmonic distortion. The proposed solar inverter system comprises several elements, including a photovoltaic array, a Relift Luo Converter (RLC), and a 15-Level Switch-Minimized Multilevel Inverter (15LSMMI), alongside the CMAES-CMBO-HFF-2DoF-FOTIDC controller. The choice of the RLC over the others from the category stems from its capability to mitigate parasitic capacitance effects, achieve high efficiency, increase power density, reduce ripple voltage magnitude, and lower duty cycle requirements. This control strategy employs a fuzzy-logic-based, optimized 2DoF fractional-order tilt integral derivative controller (2DoF-FOTIDC). The CMAES-CMBO algorithm optimizes the controller's parameters. Comparative analysis of the CMAES-CMBO-HFF-2DoF-FOTIDC controller with other state-of-the-art controllers demonstrates its superior performance and effectiveness. Additionally, the manuscript explores the implementation of the Random Pulse Position Pulse Width Modulation (RPPPWM) method alongside the proposed approach. The proposed GISIS aims to address harmonic distortion reduction, alongside improvements in the performance of solar inverters, robustness, stability, and enhanced capabilities to deal with system uncertainties.